Anatomic characteristics of the lacrimal sac and adjacent bony structures–a computed tomographic-dacryocystography research - Xin-Han Cui; Yan-Wen Fang; Li-Min Zhang; Ji-Ni Qiu; Chao-Ran Zhang; Yan Wang (International Journal of Ophthalmology)
AIM: To describe the anatomic characteristics of the lacrimal sac and its adjacent bone structures and to provide surgical recommendations for endoscopic dacryocystorhinostomy (EN-DCR). METHODS: This retrospective comparative study involved 118 sides with complete nasolacrimal duct obstruction and 83 unaffected sides from 126 patients. Computed tomographic-dacryocystography (CT-DCG) scans were performed before lacrimal surgery, and image reconstruction was used to obtain continuous 0.75-mm axial, coronal, and segmental sections for review. The morphology of the lacrimal sac and its relationship with adjacent bony structures were determined for measurement, as well as the obstructed location. RESULTS: The height of the lacrimal sac was 12.99±2.10 mm in this study. The operculum of the middle turbinate (OMT) was located vertically in the lower third of the lacrimal sac. Horizontally, the junction between the maxillary bone and the lacrimal bone (MB-LB) was close to, mostly (60.2%) posterior to, the lacrimal sac. The uncinate process was more frequently attached to the lacrimal bones (75.1%). The obstructions were generally located around the entrance of the nasolacrimal duct (NLD). However, some were placed higher, with 7.63% blocked not lower than the OMT. There was a negative correlation between the diameter of the lacrimal sac and the level of obstruction (r= -0.35, P<0.01). CONCLUSION: In this study, the OMT and MB-LB can be served as the landmarks in EN-DCR. Partial uncinectomy should be performed in most cases. The obstructions were generally located around the entrance of the NLD, but some extreme individual variations strongly implies the importance of CT-DCG scanning before surgery.